What is the answer for question 2. a)?

http://postimg.org/image/scirn1jtt/

### 1 Answer | Add Yours

`3log_(5)a+4log_(5)b-2log_(5)c` (given)

`=log_(5)a^3+log_(5)b^4-log_(5)c^2` (`n log_(b)m=log_(b)m^n` )

`=log_(5)(a^3*b^4)-log_(5)c^2` (`log_(b)m+log_(b)n=log_(b)mn` )

`=log_(5)((a^3b^4)/c^2)` (`log_(b)m-log_(b)n=log_(b)m/n` )

**Hence the required answer is** `log_(5)((a^3b^4)/c^2)` .

**Sources:**

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes